Low-density flexible environment-friendly moisture-proof thermal insulation composite material as well as preparation method and application thereof

By combining natural hemp fibers with organic silicone solution, low-density, flexible, environmentally friendly, moisture-proof, thermal insulation composite materials are prepared, which solves the problems of low strength and complex preparation of existing materials, and achieves high flexibility and low density , environmentally friendly thermal insulation effect, suitable for aerospace field.

CN119286049APending Publication Date: 2025-01-10HARBIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411616568.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing insulation materials have low strength, easy aging and fire safety hazards. Inorganic materials have high brittleness and high water absorption. The preparation process of aerogel materials is complex and costly, which limits its large-scale application in the field of insulation and insulation. .

Method used

Pretreatment with natural hemp fibers, combined with alkali solution and hydrogen peroxide solution, and then mixed with organosiloxane solution to prepare low-density flexible environmentally friendly moisture-proof and thermal insulation composite materials through sol-gel reaction, using multi-stage of hemp fibers The fibrous structure and hydrophobic properties of organosiloxane form high flexibility, low density aerogel composites.

Benefits of technology

It significantly improves the flexibility and thermal insulation performance of the material, reduces production costs, and has environmentally friendly and green characteristics. It is suitable for thermal protection materials in aerospace and other fields. It overcomes the brittleness and adaptability problems of existing materials and is suitable for large-scale Industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286049A_ABST
    Figure CN119286049A_ABST
Patent Text Reader

Abstract

The invention discloses a low-density flexible environment-friendly moisture-proof thermal insulation composite material as well as a preparation method and application thereof, and belongs to the technical field of thermal protection composite materials and preparation thereof. The problem that an existing heat preservation and insulation material is poor in flexibility and heat insulation performance is solved. Natural fibrilia is pretreated to improve the flexibility and reaction activity of the natural fibrilia, and then the natural fibrilia is compounded with flexible polysiloxane aerogel through a sol-gel and normal-pressure drying method, so that the aerogel composite material with low density, high flexibility and good heat preservation and heat insulation properties is obtained. The prepared low-density flexible environment-friendly moisture-proof heat preservation and heat insulation composite material has the advantages of being excellent in flexibility and heat insulation performance, easy to fold, unfold and deform, large in failure strain, insensitive to damage and good in adaptability to surrounding structures, and the problems that an existing heat preservation and heat insulation material is large in brittleness and poor in adaptability to the surrounding structures are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a low-density flexible environmentally friendly moisture-proof heat-insulating composite material and a preparation method and application thereof, belonging to the technical field of heat-protective composite materials and preparation thereof. Background Art

[0002] Existing organic thermal insulation materials such as EPS polystyrene boards, XPS polystyrene boards and rigid foam polyurethane boards with excellent thermal insulation performance have the advantages of low strength, easy aging during use and certain fire safety hazards, while inorganic thermal insulation materials such as foamed cement boards, foamed ceramic insulation boards, foam glass boards with high strength and good heat resistance are relatively brittle, have high water absorption, complex preparation technology and relatively high production energy consumption.

[0003] Aerogel and its composite materials have low density, three-dimensional nano-network structure, extremely low thermal conductivity and good mechanical properties, and excellent comprehensive performance. They can provide efficient heat protection, heat insulation and thermal insulation protection for service personnel, equipment and components in extreme environments in the aerospace field. Existing aerogel protective composite materials have the problems of expensive raw materials for reinforcing phase fibers, lengthy and complicated synthesis and preparation processes, especially the solvent replacement production process, which will also produce a large amount of organic solution pollutants, and supercritical drying or freeze drying leads to high production costs, which limits their large-scale application in the field of thermal insulation.

[0004] As a representative of biomass fibers, hemp fiber has multi-level fiber fine structure, high surface chemical reaction activity, high specific strength, high specific stiffness, moderate elongation at break and other mechanical properties. It has the advantages of wide source, low price, renewable, and degradable. It has a wide range of applications in civil construction, automotive interior, medicine and health, etc. The composite material obtained by using hemp fiber to reinforce aerogel can significantly reduce the cost of raw materials, enhance mechanical properties, improve thermal insulation performance, and have environmental protection and green characteristics. Therefore, it is very necessary to provide a low-density, flexible, environmentally friendly, moisture-proof, thermal insulation aerogel material using hemp fiber, which has a wide source of raw materials, non-toxic and green ingredients, low preparation cost, and is suitable for industrial expansion production. Summary of the invention

[0005] In view of the above technical problems existing in the existing thermal insulation aerogel materials, the present invention provides a low-density flexible, environmentally friendly, moisture-proof, thermal insulation composite material and a preparation method and application thereof.

[0006] The technical solution of the present invention:

[0007] One of the purposes of the present invention is to provide a method for preparing a low-density flexible environmentally friendly moisture-proof thermal insulation composite material, the method comprising the following steps:

[0008] (1) firstly, soaking natural hemp fiber in an alkaline solution and a hydrogen peroxide solution in sequence, then neutralizing and rinsing with an acid solution, and then washing and drying in sequence to obtain delignified hemp fiber;

[0009] (2) mixing delignified hemp fibers and the organosiloxane solution, and stirring to obtain a slurry;

[0010] (3) placing the slurry in a molding mold, heating it in a closed manner to perform a sol-gel reaction and an aging treatment to obtain a wet gel composite material, and drying it to obtain a low-density flexible, environmentally friendly, moisture-proof, thermal insulation composite material.

[0011] It is further defined that (1) the alkaline solution is a mixture of NaOH, Na2SO3, fatty alcohol polyoxyethylene ether and water in a mass ratio of (1-10):(1-3):(1-4):100, and the immersion treatment temperature in the alkaline solution is 40-120°C and the time is 10-120 min.

[0012] It is further defined that the hydrogen peroxide solution in (1) is a mixture of H2O2 and water in a mass ratio of (1-5):100, and the immersion treatment temperature in the hydrogen peroxide solution is 0-90°C and the time is 30-90 minutes.

[0013] It is further defined that (1) the neutralizing acid solution is sulfuric acid, hydrochloric acid or nitric acid, the pH value is 5 to 6, the neutralization and rinsing treatment temperature of the acid solution is room temperature, and the rinsing time is 10 to 30 minutes.

[0014] It is further defined that the natural hemp fiber in (1) is a mixture of one or more of ramie, jute, hemp, hemp, flax, ramie and kenaf, and has a length of 0.5-15 cm.

[0015] It is further defined that the organosiloxane solution in (2) is prepared by mixing acetic acid or oxalic acid, urea, a surfactant, siloxane and water in a mass ratio of 0.03:20:5:(25-40):100.

[0016] It is further defined that the surfactant is hexadecyltrimethylammonium chloride or hexadecyltrimethylammonium bromide; the siloxane is a mixture of dialkoxysilane and trialkoxysilane in a mass ratio of 3:2, the dialkoxysilane is dimethyldimethoxysilane or dimethyldiethoxysilane, and the trialkoxysilane is methyltrimethoxysilane or methyltriethoxysilane.

[0017] It is further defined that the sealed heating temperature in (3) is 60-80°C for 24-72 hours, and the drying temperature is 80-110°C for 12-24 hours. The present invention requires the sol-gel reaction and aging treatment temperature to be 60-80°C. The main purpose is to control the slow decomposition of urea to provide a weak alkaline mild environment to catalyze the polymerization of polyorganosiloxane and reduce the crosslinking degree, thereby improving the flexibility of the polyorganosiloxane macromolecular chain. If the catalyst alkalinity and the reaction temperature are too high, the polyorganosiloxane crosslinking degree is too high, resulting in poor flexibility.

[0018] The second object of the present invention is to provide a low-density flexible environmentally friendly moisture-proof thermal insulation composite material prepared by the above method, wherein the composite material uses delignified hemp fiber as a reinforcement and a flexible polysiloxane aerogel as a matrix; wherein the mass fraction of the delignified hemp fiber is 10-90%.

[0019] The third object of the present invention is to provide an application of the above-mentioned low-density flexible environmentally friendly moisture-proof heat-insulating composite material, specifically as a thermal protection material in the aerospace field.

[0020] Beneficial effects:

[0021] The present invention pre-treats natural hemp fibers to improve their flexibility and reactivity, and then compounds them with flexible polyorganosiloxane aerogels through sol-gel and atmospheric pressure drying methods to obtain a low-density, high-flexibility, and good thermal insulation aerogel composite material. Compared with the prior art, the present invention has at least the following advantages:

[0022] (1) The present invention first soaks the hemp fiber in an alkaline solution mixed with NaOH, Na2SO3, fatty alcohol polyoxyethylene ether and water. In the alkaline treatment solution, NaOH can destroy the structure of lignin and hemicellulose, causing them to undergo alkaline hydrolysis reaction. However, a NaOH solution with too high a concentration will damage the cellulose that provides strength in the hemp fiber and reduce the strength of the hemp fiber, while a NaOH solution with too low a concentration cannot achieve the effect of destroying cellulose. Therefore, the present invention uses NaOH and Na2SO3 in a compound manner, and utilizes Na2SO3 to undergo a sulfonation reaction with lignin to generate soluble lignin sulfonate, which further promotes the dissolution of lignin. Na2SO3 has a reducing property and can reduce the oxidative degradation of cellulose. Under the combined action of the two, the rate and efficiency of the alkaline hydrolysis reaction for removing lignin, hemicellulose and non-cellulose substances are improved. NaOH and Na2SO3 enhance the removal effect of lignin, hemicellulose and non-cellulose substances by promoting each other. This synergistic effect not only improves the processing efficiency, but also helps to protect the cellulose body and maintain the strength and integrity of the fiber, thereby optimizing the processing process of the hemp fiber, so that the natural hemp fiber bundle composed of fibrils is opened, and can better react with organic silane in subsequent processing to obtain a composite material with better bonding. At the same time, the alkaline environment provided by NaOH and Na2SO3 allows the addition of fatty alcohol polyoxyethylene ether to more effectively remove non-cellulose substances such as wax and pectin on the surface of hemp fibers, and adjust the hydrophilicity of the surface of hemp fibers, so that hemp fibers can be more evenly dispersed in the solution. At the same time, fatty alcohol polyoxyethylene ether is biodegradable and has the advantages of being green and environmentally friendly. Moreover, under alkaline conditions, the permeability of fatty alcohol polyoxyethylene ether can help the alkaline solution to be better distributed in the fiber, making it easier to remove lignin, thereby improving the removal efficiency of lignin and helping to improve the flexibility and hydrophilicity of the fiber. In addition, fatty alcohol polyoxyethylene ether can not only promote the degradation of more hydrophilic hemicellulose, but also is beneficial to maintaining a high cellulose retention rate, ensuring the strength and flexibility of the treated hemp fiber. At the same time, fatty alcohol polyoxyethylene ether can react with the hydroxyl groups exposed on the surface of cellulose in the hemp fiber under alkaline conditions to be compounded on the fiber surface, and further react with organosilane in the subsequent sol-gel process to play a bridging role to connect the hemp fiber and organosilane, so that the hemp fiber and organosilane are connected through the long chain of fatty alcohol polyoxyethylene ether, preventing excessive cross-linking of organosilane on the fiber surface, achieving flexible matching of fiber and polyorganosiloxane at the interface, and preparing a composite material with good flexibility, thereby improving the rebound performance of the composite material.

[0023] (2) The present invention uses a hydrogen peroxide solution to oxidize the hemp fiber treated with an alkaline solution, thereby oxidizing the lignin and hemicellulose remaining in the fiber, thereby achieving regulation of the lignin and hemicellulose content in the fiber.

[0024] (3) The polyorganosiloxane aerogel synthesized by the present invention using alkyl-containing dialkoxysilane and trialkoxysilane as precursors has hydrophobic or even super-hydrophobic properties (contact angle > 150°) and does not require complicated hydrophobic treatment. Using it as a matrix makes the low-density flexible, environmentally friendly moisture-proof thermal insulation composite material exhibit the advantages of moisture-proof, anti-fouling and self-cleaning, thereby expanding the application of thermal insulation in humid environments.

[0025] (4) The low-density flexible, environmentally friendly, moisture-proof, thermal insulation composite material prepared by the present invention has excellent flexibility and thermal insulation performance, is easy to fold and deform, has a large failure strain and is insensitive to damage, and has good adaptability to surrounding structures, overcoming the problems of existing thermal insulation materials such as high brittleness and poor adaptability to surrounding structures. It can be prepared using standard parts and can be cut on-site during construction according to the requirements of specific application scenarios. It is particularly convenient for thermal insulation construction of complex structures, can greatly improve construction efficiency, shorten construction period, and reduce manpower requirements and logistics costs.

[0026] (5) The present invention adopts the mature sol-gel method and simple atmospheric pressure drying to prepare aerogel composite materials. The technology is simple, the operation is convenient, and it is suitable for large-scale industrial production. It is easy to promote and use. It is suitable for heat insulation applications in multiple fields such as construction, industry, transportation, cold chain goods, etc. It can also be used as a thermal protection material in the aerospace field (such as hypersonic aircraft, ground launch systems). BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a SEM photo of natural hemp fiber;

[0028] Figure 2 This is a SEM photo of the delignified hemp fiber prepared in Example 1;

[0029] Figure 3 This is a SEM photo of the low-density flexible environmentally friendly moisture-proof thermal insulation material prepared in Example 1;

[0030] Figure 4 This is the cyclic compression curve of the low-density flexible environmentally friendly moisture-proof thermal insulation material prepared in Example 1;

[0031] Figure 5 This is a real picture of the low-density flexible environmentally friendly moisture-proof thermal insulation material prepared in Example 2 being attached to the corner of the wall;

[0032] Figure 6 This is a physical picture of the low-density flexible environmentally friendly moisture-proof heat-insulating material prepared in Example 2 being attached to a stainless steel pipe (diameter 30 mm);

[0033] Figure 7This is a photo of the hydrophobic performance test of the low-density flexible environmentally friendly moisture-proof thermal insulation material prepared in Example 6;

[0034] Figure 8 This is a contact angle test diagram of the low-density flexible environmentally friendly moisture-proof thermal insulation material prepared in Example 1;

[0035] Fig. 9 This is an anti-pollution test chart of the low-density flexible environmentally friendly moisture-proof thermal insulation material prepared in Example 1;

[0036] Fig.10 This is a liquid nitrogen insulation test result diagram of the low-density flexible environmentally friendly moisture-proof thermal insulation material prepared in Example 1;

[0037] Fig.11 This is a test chart of the thermal insulation performance of the low-density flexible, environmentally friendly, moisture-proof, thermal insulation material prepared in Example 1. DETAILED DESCRIPTION

[0038] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0039] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0040] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0041] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art, and the purity of the solid and liquid reagents used is analytically pure.

[0042] It should be noted that the performance tests in the following examples and comparative examples refer to the following standards:

[0043] Static contact angle: The static contact angle was measured using a video optical contact angle meter according to the sessile drop method.

[0044] Room temperature thermal conductivity: refer to ISO22007-2 standard.

[0045] Compression Strength: Non-destructive compression strength data were obtained by cyclic compression testing under 40% compressive strain.

[0046] Compression recovery rate: the thickness retention rate obtained by performing 10 cycles of compression-unloading test under 40% compression conditions.

[0047] Compression recovery rate: the thickness retention rate obtained by performing 10 cycles of compression-unloading test under 40% compression conditions.

[0048] Insulation internal and back temperature: Insulation was performed on the surface of the liquid nitrogen tank for 30 minutes to obtain the back temperature data at 10mm and 20mm from the tank surface.

[0049] Insulation internal and back temperature: Heating was performed on a 200°C ceramic heating plate for 30 minutes to obtain back temperature data at 10 mm and 35 mm from the heating surface.

[0050] Example 1

[0051] The specific process of preparing the low-density flexible environmentally friendly moisture-proof thermal insulation material in this embodiment is as follows:

[0052] S1. Mix 5 g of NaOH, 2 g of Na2SO3, 1 g of fatty alcohol polyoxyethylene ether and 100 g of water to obtain an alkali treatment solution, remove impurities from 0.5 g of natural jute fiber, cut it into 1 cm length, immerse it in the alkali treatment solution, and treat it at 120° C. for 120 min to obtain alkali-treated jute fiber.

[0053] S2. Mix 2 g of hydrogen peroxide and 100 g of water to obtain a H2O2 solution, immerse the alkali-treated hemp fiber in the H2O2 solution, and treat it at 90° C. for 90 min to obtain oxidized hemp fiber.

[0054] S3. Nitric acid and water are mixed to obtain 200 ml of an acid treatment solution with a pH of 5. One gram of oxidized hemp fiber is neutralized and rinsed with the acid treatment solution at room temperature for 15 minutes until the pH is 7, thereby obtaining neutral hemp fiber.

[0055] S4. After washing the neutral flax fiber for multiple times, drying it at 65° C. to obtain delignified flax fiber.

[0056] S5, 0.03g acetic acid, 33.34g urea, 6.06g hexadecyltrimethylammonium bromide, 33g siloxane and 100g water are mixed to obtain an organosiloxane solution, wherein the siloxane is a mixture of dialkoxysilane and trialkoxysilane in a mass ratio of 3:2, the dialkoxysilane is dimethyldiethoxysilane, and the trialkoxysilane is methyltrimethoxysilane.

[0057] S6. Place 0.5 g of delignified hemp fiber in 200 mL of the organosiloxane solution, and mix by vigorous stirring to obtain an organosiloxane solution-delignified hemp fiber mixture slurry.

[0058] S7. The mixture slurry is transferred to a molding mold, and heated to 65° C. in a sealed state for 72 hours to perform a sol-gel reaction and an aging treatment to obtain a delignified hemp fiber reinforced polyorganosiloxane wet gel composite material.

[0059] S8. Place the obtained delignified hemp fiber reinforced polysiloxane wet gel composite material in an oven, and dry it at 80° C. for 24 hours under normal pressure to obtain a low-density flexible, environmentally friendly, moisture-proof, thermal insulation composite material.

[0060] Example 2

[0061] The difference between this embodiment and embodiment 1 is that the treatment time of the alkaline treatment solution in S1 is 60 minutes, and the other process steps and parameter settings are the same as those in embodiment 1.

[0062] Example 3

[0063] The difference between this embodiment and embodiment 1 is that the treatment temperature of the alkaline treatment solution in S1 is 60° C., and the remaining process steps and parameter settings are the same as those in embodiment 1.

[0064] Example 4

[0065] The difference between this embodiment and embodiment 1 is that the alkaline treatment solution in S1 is a mixture of 10g NaOH, 2g Na2SO3, 1g fatty alcohol polyoxyethylene ether and 100g water, and the remaining process steps and parameter settings are the same as those in embodiment 1.

[0066] Example 5

[0067] The difference between this embodiment and embodiment 1 is that the H2O2 solution treatment time of S1 is 50 min.

[0068] Example 6

[0069] The difference between this embodiment and embodiment 1 is that hydrochloric acid is used to replace nitric acid in S3, and the remaining process steps and parameter settings are the same as those in embodiment 1.

[0070] Example 7

[0071] The difference between this embodiment and embodiment 1 is that in S3, nitric acid and water are mixed to obtain an acid treatment solution with a pH of 5.5, and the remaining process steps and parameter settings are the same as those in embodiment 1.

[0072] Example 8

[0073] The difference between this embodiment and embodiment 1 is that the neutralization and rinsing time in S3 is 30 minutes, and the other process steps and parameter settings are the same as those in embodiment 1.

[0074] Example 9

[0075] The difference between this embodiment and embodiment 1 is that in S1, the natural hemp fibers are cut into 2 cm lengths after removing impurities, and the remaining process steps and parameter settings are the same as those in embodiment 1.

[0076] Example 10

[0077] The difference between this embodiment and embodiment 1 is that in S1, the natural hemp fibers are cut into 15 cm lengths after removing impurities, and the remaining process steps and parameter settings are the same as those in embodiment 1.

[0078] Embodiment 11

[0079] The difference between this embodiment and embodiment 1 is that the organosiloxane solution in S5 is prepared by mixing 0.03 g acetic acid, 33.34 g urea, 6.06 g hexadecyltrimethylammonium bromide, 40 g siloxane and 100 g water, and the remaining process steps and parameter settings are the same as those in embodiment 1.

[0080] Example 12

[0081] The difference between this embodiment and embodiment 1 is that the dialkoxysilane in S5 is dimethyldiethoxysilane, and the remaining process steps and parameter settings are the same as those in embodiment 1.

[0082] Example 13

[0083] The difference between this embodiment and embodiment 1 is that the trialkoxysilane in S5 is methyltriethoxysilane, and the remaining process steps and parameter settings are the same as those in embodiment 1.

[0084] Embodiment 14

[0085] The difference between this embodiment and embodiment 1 is that oxalic acid is used in S5 instead of acetic acid, and the remaining process steps and parameter settings are the same as those in embodiment 1.

[0086] Embodiment 15

[0087] The difference between this embodiment and embodiment 1 is that the delignified hemp fiber in S6 is 2 g, and the other process steps and parameter settings are the same as those in embodiment 1.

[0088] Example 16

[0089] The difference between this embodiment and embodiment 1 is that the temperature of the sol-gel reaction and aging treatment in S7 is 80° C. and the time is 48 h. The other process steps and parameter settings are the same as those in embodiment 1.

[0090] Embodiment 17

[0091] The difference between this embodiment and embodiment 1 is that the drying treatment temperature in S8 is 90° C. and the time is 20 h. The other process steps and parameter settings are the same as those in embodiment 1.

[0092] Comparative Example 1

[0093] The difference between this comparative example and Example 1 is that natural hemp fiber is used to replace the delignified hemp fiber in S6, and the remaining process steps and parameter settings are the same as those in Example 1.

[0094] Comparative Example 2

[0095] The difference between this comparative example and Example 1 is that the amount of hexadecyltrimethylammonium bromide added in S5 is 0 g, and the remaining process steps and parameter settings are the same as those in Example 1.

[0096] Comparative Example 3

[0097] The difference between this comparative example and Example 1 is that the amount of Na2SO3 added in S1 is 0g, and the remaining process steps and parameter settings are the same as those in Example 1.

[0098] Comparative Example 4

[0099] The difference between this comparative example and Example 1 is that the alkaline treatment solution in S1 is a mixture of 5g NaOH, 5g Na2SO3, 1g fatty alcohol polyoxyethylene ether and 100g water, and the remaining process steps and parameter settings are the same as those in Example 1.

[0100] Comparative Example 5

[0101] The difference between this comparative example and Example 1 is that the alkaline treatment solution in S1 is a mixture of 20g NaOH, 5g Na2SO3, 1g fatty alcohol polyoxyethylene ether and 100g water, and the remaining process steps and parameter settings are the same as those in Example 1.

[0102] Comparative Example 6

[0103] The difference between this comparative example and Example 1 is that the amount of fatty alcohol polyoxyethylene ether added in S1 is 0 g, and the remaining process steps and parameter settings are the same as those in Example 1.

[0104] Comparative Example 7

[0105] The difference between this comparative example and Example 1 is that the H2O2 solution in S2 is a mixture of 5g hydrogen peroxide and 100g water (mass ratio is 5:100), and the remaining process steps and parameter settings are the same as those in Example 1.

[0106] Comparative Example 8

[0107] The difference between this embodiment and embodiment 1 is that the temperature of the sol-gel reaction and aging treatment in S7 is 40° C. and the time is 48 h. The other process steps and parameter settings are the same as those in embodiment 1.

[0108] Effect example

[0109] (1) The microscopic morphology of the natural hemp fiber and the delignified hemp fiber obtained in Example 1 was characterized. The SEM images were as follows: Figure 1 and 2 As shown in the figure, it can be seen that the delignified hemp fiber has a lower lignin content between the fibrils than the natural hemp fiber, and there are a large number of submicron pores between the fibrils. The freedom of relative movement between the fibrils is higher, which provides space for the introduction of polyorganosiloxane aerogel between the fibrils.

[0110] (2) The microscopic morphology of the low-density flexible environmentally friendly moisture-proof thermal insulation material obtained in Example 1 was characterized, and the SEM photos are as follows Figure 3 As shown by Figure 3 It can be seen that the delignified hemp fibers of the obtained low-density flexible environmentally friendly moisture-proof thermal insulation material are randomly distributed in the aerogel matrix in all directions, and the pores between the fibrils are bonded by the aerogel to form a fibril-aerogel-fibril interface structure.

[0111] (3) The compression resilience of the low-density flexible environmentally friendly moisture-proof thermal insulation material obtained in Example 1 was characterized. The test results are as follows: Figure 4 As shown by Figure 4 It can be seen that the low-density flexible environmentally friendly moisture-proof thermal insulation material has good compression resilience and can be repeatedly compressed and rebounded under 70% compression strain. The irreversible deformation mainly occurs in the first 10 times, and the compression and rebound behavior tends to be stable in the later period.

[0112] (4) The bending deformation ability and adaptability of the low-density flexible environmentally friendly moisture-proof thermal insulation material obtained in Example 1 to the surrounding structure were characterized. The test results are as follows: Figure 5 and Figure 6 As shown in the figure, it can be seen that the material with a thickness of 8mm can fit the corners of the wall (radius ~4mm) and the bending and deformation of the stainless steel pipe (diameter 30mm) without damaging the structure.

[0113] (5) The anti-fouling performance of the low-density flexible environmentally friendly moisture-proof thermal insulation material obtained in Example 1 was characterized by standard methods. The results are as follows: Fig. 9 As shown, the low-density flexible environmentally friendly moisture-proof thermal insulation material has good anti-pollution ability to dust simulated by carbon powder, and can be quickly washed clean by simulated rainwater without residue to achieve self-cleaning.

[0114] (6) The thermal insulation performance of the low-density flexible environmentally friendly moisture-proof thermal insulation material obtained in Example 1 was characterized. Specifically, the low-density flexible environmentally friendly moisture-proof thermal insulation material was processed into a barrel-shaped component with a thickness of 20 mm, and a liquid nitrogen tank was placed in the barrel. The temperature data of the back side at 10 mm and 20 mm from the tank surface were obtained for 30 minutes. Fig.10 As shown in the figure, it can be seen that the low-density flexible environmentally friendly moisture-proof thermal insulation material shows excellent thermal insulation ability for the liquid nitrogen tank. In an environment where liquid nitrogen provides -196°C, the temperature on the back side 10mm and 20mm away from the tank surface drops to only -53.4°C and -7.9°C respectively after 30 minutes.

[0115] (7) The thermal insulation performance of the low-density flexible environmentally friendly moisture-proof thermal insulation material obtained in Example 1 was characterized. Specifically, the low-density flexible environmentally friendly moisture-proof thermal insulation material was processed into a flat plate component with a thickness of 35 mm, and heated on a 200° C. ceramic heating plate for 30 minutes to obtain the back temperature data at 10 mm and 35 mm from the heating surface. The results are as follows Fig.11 As shown by Fig.11 It can be seen that the low-density flexible environmentally friendly moisture-proof thermal insulation material has excellent thermal insulation capabilities. After the ceramic plate is heated at 200°C for 30 minutes, the temperature rise on the back side 10mm and 35mm away from the tank surface is only 129.7°C and 35.6°C respectively.

[0116] (8) The hydrophobicity of the low-density flexible environmentally friendly moisture-proof thermal insulation material obtained in Example 5 was tested. The results are as follows: Figure 7 and 8 As shown in the figure, it can be seen that the low-density flexible environmentally friendly moisture-proof thermal insulation material has excellent hydrophobicity, which is conducive to long-term thermal insulation applications in humid environments, making the material highly adaptable to extreme service environments. Further analysis Figure 8 It can be seen that the static contact angle of the low-density flexible environmentally friendly moisture-proof thermal insulation material obtained in Example 1 reaches 155.32°, achieving surface super-hydrophobicity.

[0117] (9) The basic properties of the low-density flexible environmentally friendly moisture-proof thermal insulation composite materials obtained in Examples 1 to 17 and Comparative Examples 1 to 8 were tested, and the results are shown in the following table:

[0118]

[0119]

[0120]

[0121]

[0122] The “—” in the table indicates that the prepared composite material does not meet the requirements and no further performance test is performed or relevant performance test cannot be performed.

[0123] As can be seen from the above table, by adding different raw material components, adjusting the raw material ratio and changing the process conditions, Examples 1 to 4 can obtain a series of composite materials with low density, flexibility, moisture resistance, heat preservation and heat insulation characteristics. The composite material has good thermal insulation, low internal temperature rise and slow heating rate under the high temperature environment of liquid nitrogen insulation and ceramic heating plate, and has outstanding thermal insulation ability while having good moisture resistance, anti-fouling and self-cleaning properties. Compared with Example 1, the composite material prepared from natural hemp fiber without delignification treatment in Comparative Example 1 has relatively poor flexibility and thermal insulation properties. This is mainly because the lignin bonded between the fibrils of the natural hemp fiber is partially or completely removed after the solution treatment, which improves the freedom of relative movement between the fibrils in the hemp fiber, avoids the local transition deformation and even fracture damage of the fibrils during the deformation of the composite material, and improves the flexibility of the delignified hemp fiber. The space between the fibrils originally occupied by lignin forms a large number of pores after the lignin is removed. Mixing with the organosiloxane solution is conducive to the infiltration of the organosiloxane solution. After the sol-gel reaction, the solution impregnated between the fibrils is converted into a flexible polyorganosiloxane aerogel, forming a fibril-aerogel-fibril interface structure in which the aerogel bonds the fibrils. The newly exposed fibril surface is rich in a large number of functional groups such as hydroxyl groups, which undergo dehydration and condensation with the silanol groups formed by the hydrolysis of the organosiloxane to form interfacial chemical bonds to enhance the interfacial chemical bonding effect. During the deformation of the composite material, the load is efficiently transferred between the fibrils, and a flexible buffer is formed to coordinate the microscopic deformation of the fibrils and reduce the impact and friction between the fibers to avoid fiber damage, thereby improving the strength and flexibility of the composite material. The fibril-aerogel-fibril interface structure gives the composite material a more refined microscopic morphology, interface structure and micro-nanoscale pores, providing a more complex solid-phase communication path during the heating process to limit solid-phase heat conduction and inhibit heat convection, hindering the transfer of heat inside the composite material to form efficient thermal insulation. Compared with Example 1, the composite material prepared in Comparative Example 2 using a rigid polyorganosiloxane aerogel matrix has a reduced failure strain and contact angle due to the brittleness and hydrophilicity of the aerogel.

[0124] Further contact angles show that the static contact angle of the low-density flexible environmentally friendly moisture-proof thermal insulation material provided in Example 1 reaches 155.32°, achieving surface super-hydrophobicity, while the contact angle of the composite material in Comparative Example 1 is only 113.18°, the contact angle of the composite material in Example 2 is 131.43°, and the contact angle of the composite material in Example 3 is 137.91°. This is mainly because the hydrophobicity of lignin is significantly better than that of hemicellulose. The aromatic rings and fewer hydrophilic groups in the lignin structure make lignin difficult to dissolve in water, while hemicellulose is a polysaccharide structure containing multiple hydroxyls and has stronger hydrophilicity. Therefore, compared with Example 1, the delignified hemp fiber in Example 3 has less lignin content, but more hemicellulose content, resulting in the contact angle of the composite material in Example 3 being smaller than that in Example 1. The delignified hemp fiber in Example 2 has only a slight change in hemicellulose content compared with the delignified hemp fiber in Example 1, but the lignin content in Example 1 is less, resulting in the hydrophobic effect of the composite material in Example 1 being better than that in Example 2.

[0125] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing a low-density flexible environmentally friendly moisture-proof thermal insulation composite material, characterized in that: include: (1) firstly, soaking natural hemp fiber in an alkaline solution and a hydrogen peroxide solution in sequence, then neutralizing and rinsing with an acid solution, and then washing and drying in sequence to obtain delignified hemp fiber; (2) mixing delignified hemp fibers and the organosiloxane solution, and stirring to obtain a slurry; (3) placing the slurry in a molding mold, heating it in a closed manner to perform a sol-gel reaction and an aging treatment to obtain a wet gel composite material, and drying it to obtain a low-density flexible, environmentally friendly, moisture-proof, thermal insulation composite material.

2. The preparation method according to claim 1, characterized in that: (1) The medium alkaline solution is prepared by mixing NaOH, Na2SO3, fatty alcohol polyoxyethylene ether and water in a mass ratio of (1-10):(1-3):(1-4):

100. The immersion treatment temperature of the alkaline solution is 40-120°C and the time is 10-120 minutes.

3. The preparation method according to claim 1, characterized in that: (1) The hydrogen peroxide solution is prepared by mixing H2O2 and water in a mass ratio of (1-5):

100. The immersion treatment temperature of the hydrogen peroxide solution is 0-90°C and the time is 30-90 minutes.

4. The preparation method according to claim 1, characterized in that: (1) The neutralized acid solution is sulfuric acid, hydrochloric acid or nitric acid with a pH value of 5 to 6. The neutralization and rinsing treatment temperature is room temperature and the rinsing time is 10 to 30 minutes.

5. The preparation method according to claim 1, characterized in that: (1) The natural hemp fiber is a mixture of one or more of ramie, jute, hemp, hemp, flax, ramie, and kenaf, with a length of 0.5-15 cm.

6. The preparation method according to claim 1, characterized in that: (2) The organic siloxane solution is prepared by mixing acetic acid or oxalic acid, urea, a surfactant, siloxane and water in a mass ratio of 0.03:20:5:(25-40):

100.

7. The preparation method according to claim 6, characterized in that: The surfactant is hexadecyltrimethylammonium chloride or hexadecyltrimethylammonium bromide; the siloxane is prepared by mixing dialkoxysilane and trialkoxysilane in a mass ratio of 3:2, the dialkoxysilane is dimethyldimethoxysilane or dimethyldiethoxysilane, and the trialkoxysilane is methyltrimethoxysilane or methyltriethoxysilane.

8. The preparation method according to claim 1, characterized in that: (3) The sealed heating temperature is 60-80°C for 24-72 hours, and the drying temperature is 80-110°C for 12-24 hours.

9. A low-density flexible environmentally friendly moisture-proof thermal insulation composite material obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The composite material uses delignified hemp fiber as a reinforcement and flexible polyorganosiloxane aerogel as a matrix; the mass fraction of the delignified hemp fiber is 10-90%.

10. An application of the low-density flexible environmentally friendly moisture-proof thermal insulation composite material according to claim 9, characterized in that: Used as thermal protection material in the aerospace field.